KOMPOSISI VEGETASI MANGROVE BERDASARKAN STRATA PERTUMBUHAN DI TELUK SEREWEH, KABUPATEN LOMBOK TIMUR, NUSA TENGGARA BARAT - Firman Ali Rahman (Biology Education Department, Faculty of Teacher Training and Education, University of Nahdlatul Wathan Mataram - Indonesia, 2020)
Mangroves are vegetations that are still affected by tides with unique properties and shapes, and diverse functions for living things and the environment. The purpose of this study was to determine the composition and structure of mangrove vegetation in the Sereweh bay. This research is a quantitative descriptive using the plot path method with a plot area of ​​20x20 m2 (trees), 10x10 m2 (poles), 5x5 m2 (saplings) and 2x2 m2 (seedlings). The results showed that the composition of mangrove vegetation found in the Sereweh bay was quite diverse consisting of 7 (seven) families with a total of 13 species namely: Avicennia lanata, Lumnitzera racemosa, Exceocaria agallocha, Phemphis acidula, Bruguiera gymnorrizha, Ceriop decandra, Ceriop tagal, Rhizophora, Rhizophora apiculata, Rhizophora mucronata, Rhizopora stylosa, Scyphiphora hydrophyllaceae, Sonneratia alba, and Sonneratia caseolaris. The significance value index of the seedlings stratum is dominated by Rhizophora apiculata (88.22%), Rhizopora stylosa (49.78%) and Ceriop tagal (13.93%). Whereas the the significance value index of saplings stratum was dominated by Rhizopora stylosa (43.28%), Sonneratia alba (40.89%) and Ceriop tagal (32.25%). The significance value index of the poles strata are dominated by Sonneratia alba (89.89%), Avicennia lanata (51.72%) and Rhizophora apiculata (43.94%). Whereas the significance value index tree strata were dominated by Sonneratia alba (128.01%), Sonneratia caseolaris (73.17%), and Avicennia lanata (39.81%). The Shannon-Wiener (H') diversity index of 13 species of mangrove in Sereweh Bay 1,8480 which can be categorized as quite good (medium) and the highest diversity index on all species are Rhizophora apiculata (0.3677), Rhizopora stylosa (0.3306) and Sonneratia alba (0.2565).